A longitudinal evaluation of improvements in treatment plan quality for lung cancer with volumetric modulated arc therapy. Issue 6 (1st April 2020) - Xia, Wenlong; Liu, Zhiqiang; Yan, Lingling; Han, Fei; Hu, Zhihui; Tian, Yuan; Cui, Weijie; Ren, Wenting; Guo, Chenlei; Miao, Junjie; Dai, Jianrong
Abstract: Purpose: To investigate planning time and number of optimizations in routine clinical lung cancer plans based on the plan quality improvements following each optimization. Materials and method: We selected 40 patients with lung cancer who were treated with conventional fractionated radiotherapy (CFRT). The 40 plans (divided into two groups with one or two target volumes) were completed by 9 planners using volumetric modulated arc therapy (VMAT). A planning strategy, including technique script for each group and a planning process for data collection, was introduced. The total planning time, number of optimizations, and dose–volume parameters of each plan were recorded and analyzed. A plan quality metric (PQM) was defined according to the clinical constraints. Statistical analysis of parameters of each plan following each optimization was performed for evaluating improvements in plan quality. Results: According to the clinical plans generated by different planners, the median number of optimizations of each group was 4, and the median planning time was approximately 1 h (68.6 min and 62.0 min for plans with one or two target volumes, respectively). The dose deposited in organs at risk (OARs) gradually decreased, and the PQM values gradually improved following each optimization. The improvements were significant only between adjacent optimizations from the first optimization (Opt1) to the third optimization (Opt3). Conclusion: Increasing the number of optimizations was associated with significantly improved sparing of OARs with slight effects on the dose coverage and homogeneity of target volume. Generally, based on the designed planning strategy, there was no significant improvement of the plan quality for more than three optimizations.